(untitled) (Scientific journal of the Fergana State University, 2024)
The article analyzes the structural content of professional competence in future pedagogues, the factors of formation and development of professional competence in them, and its impact on the quality of education. It has been revealed that surviving strong competition requires every professional to have professional competence and to continuously improve it.